2018
DOI: 10.1016/j.asej.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of suction/injection on steady fully developed mixed convection flow in a vertical parallel plate microchannel

Abstract: This paper examined the hydrodynamic and thermal behaviour of steady fully developed mixed convection flow in a vertical parallel-plate micro-porous-channel (MPC) in the presence of suction/injection with velocity slip and temperature jump at the boundaries. The exact solutions of the energy and momentum equations are obtained. The influence of each governing parameter on dimensionless velocity, temperature, volume flow rate, rate of heat transfer and skin friction at the micro-porous-channel surfaces is discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…In addition, increasing injection (S < 0) causes the fluid velocity to grow as shown in Figure 4. 2,6 Figures 5 and 6 represent the effect of Eckert number (Ec) on temperature and velocity profiles. It is observed that increasing Eckert number increases both fluid temperature and velocity within the channel.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, increasing injection (S < 0) causes the fluid velocity to grow as shown in Figure 4. 2,6 Figures 5 and 6 represent the effect of Eckert number (Ec) on temperature and velocity profiles. It is observed that increasing Eckert number increases both fluid temperature and velocity within the channel.…”
Section: Resultsmentioning
confidence: 99%
“…In most of the studies, nanofluids have been used as a cooling fluid to improve the heat transfer. Jha and Aina [14] reported that the volumetric flow rate increases by increasing injection and suction, while the heat transfer decreases. Also, the possibility of a return flow on the cold wall decreases with the Knudsen number.…”
Section: Introductionmentioning
confidence: 99%
“…The systems of ordinary di erential equations (9)-(10) representing the de ned ow problem along with the boundary conditions (11)- (14) are highly nonlinear. The boundary value problems are converted into initial value problem.…”
Section: Solution Proceduresmentioning
confidence: 99%
“…It is obtained that rise in values of magnetic parameter leads to increase of velocity pro le. Impact of suction/injection on porous microchannel has been studied by Jha and Aina [14]. The result depicts that rate of heat transfer increases as mixed convection parameter increases.…”
Section: Introductionmentioning
confidence: 99%